2022
DOI: 10.1155/2022/7727953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Integrated Nursing Care Based on Medical Alliance Mode on the Prevention and Treatment of Complications and Self-Efficacy of Patients with Coronary Heart Disease after PCI

Abstract: Objective. To explore the effect of integrated nursing care based on the medical alliance model on prevention and treatment of complications and self-efficacy in patients with coronary heart disease (CHD) after PCI. Methods. The data of CHD patients treated in our hospital from January 2019 to January 2021 were analyzed in this retrospective study. One hundred and twenty patients were selected as the research subjects according to the inclusion and exclusion criteria and equally split into the observation grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Self‐care ability is closely related to patient quality of life (Zhu, Liu, et al, 2021 ; Zhu, Lu, et al, 2021 ), and patients themselves play the main role in their daily management. The good self‐management ability may help patients to reduce the incidence of postoperative complications (Zhao & Wang, 2022 ). However, the self‐care ability of patients after PCI is not optimistic, and they are highly dependent on others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐care ability is closely related to patient quality of life (Zhu, Liu, et al, 2021 ; Zhu, Lu, et al, 2021 ), and patients themselves play the main role in their daily management. The good self‐management ability may help patients to reduce the incidence of postoperative complications (Zhao & Wang, 2022 ). However, the self‐care ability of patients after PCI is not optimistic, and they are highly dependent on others.…”
Section: Discussionmentioning
confidence: 99%
“…For example, self‐efficacy may influence cancer patients' pain management ability (Vilardaga et al, 2022 ), and low self‐efficacy cancer patients may be vulnerable to psychological morbidity (Howell et al, 2022 ). A study found that improving PCI patients' self‐efficacy level through external intervention would play an important role in their home care (Zhao & Wang, 2022 ). This study showed the similar results.…”
Section: Discussionmentioning
confidence: 99%
“…For patients having undergone PCI, postoperative nursing management can also improve their QOL. A study performed by Zhao et al [22] showed that integrated nursing care based on the medical alliance model can improve the self-efficacy of CHD patients having undergone PCI, enhance their self-management ability, and reduce the incidence of postoperative complications, which is conducive to improving their prognosis. Lin et al [23] studied the effect of whole-cause care in patients with acute myocardial infarction having undergone emergency PCI.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for selecting a concept is that coronary heart disease patients with high self-efficacy have stronger self-confidence in treatment, higher psychological resilience, lower risk of stress disorders, and lower anxiety or depression compared to those with low self-efficacy (Liu et al, 2018). Improving the self-efficacy among coronary heart disease patients undergoing PCI will improve self-management ability or selfcare dan decrease complication occurrence post surgery so which is conducive improve prognosis patients (Zhao & Wang, 2022).…”
Section: Select a Conceptmentioning
confidence: 99%